A potential link between the C5a receptor 1 and the β1-adrenoreceptor in the mouse heart - Khor, Kuan Hua; Moore, Tyson A.; Shiels, Ian A.; Greer, Ristan M.; Arumugam, Thiruma V.; Mills, Paul C. (Public Library of Science, 2016)
Purpose: Inflammation may contribute to the pathogenesis of specific cardiovascular diseases, but it is uncertain if mediators released during the inflammatory process will affect the continued efficacy of drugs used to treat clinical signs of the cardiac disease. We investigated the role of the complement 5a receptor 1 (C5aR1/CD88) in the cardiac response to inflammation or atenolol, and the effect of C5aR1 deletion in control of baseline heart rate in an anesthetized mouse model. Methods: An initial study showed that PMX53, an antagonist of C5aR1 in normal C57BL6/J (wild type, WT) mice reduced heart rate (HR) and appeared to have a protective effect on the heart following induced sepsis. C5aR1 knockout (CD88-/-) mice had a lower HR than wild type mice, even during sham surgery. A model to assess heart rate variability (HRV) in anesthetized mice was developed to assess the effects of inhibiting the β1-adrenoreceptor (β1-AR) in a randomized crossover study design. Results: HR and LF Norm were constitutively lower and SDNN and HF Norm constitutively higher in the CD88-/- compared with WT mice (P< 0.001 for all outcomes). Administration of atenolol (2.5 mg/kg) reduced the HR and increased HRV (P< 0.05, respectively) in the wild type but not in the CD88-/- mice. There was no shift of the sympathovagal balance post-atenolol in either strains of mice (P> 0.05), except for the reduced LF/HF (Lower frequency/High frequency) ratio (P< 0.05) at 60 min post-atenolol, suggesting increased parasympathetic tone of the heart due to the effect of atenolol administration. The HR of the WT mice were lower post atenolol compared to the CD88-/- mice (P = 0.001) but the HRV of CD88-/- mice were significantly increased (P< 0.05), compared with WT mice. Conclusion: Knockout of the C5aR1 attenuated the effect of β1-AR in the heart, suggesting an association between the β1-AR and C5aR1, although further investigation is required to determine if this is a direct or causal association.